NEW ALGORITHMS IN INDUCTION METHODS OF MONITORING THE QUALITY OF IRON-ORE RAW MATERIALS IN CONVEYERS FLOWS - Yakovlev V.L.; Molchanov O.N.; Markov A.T. (My University, 2001)
Efficiency of optimal versions of computational schemes in algorithms for magnetic-induction monitoring of magnetite iron share in ores is grounded. Total iron share in ore is directly monitored on conveyers too. Fundamentally new method for protection against noises has been offered. Parametric conversion of influence of random factors in composition of information signals from IMK-Fe induction magnetometer into ordered distribution in regression dependence fields is provided in this method. The fields are formed on basis of special functions. Practical results of the use of the algorithms have been presented.